La gouvernance territoriale du et par le paysage : observations, retours d’expériences, regards critiques - Marie-José Fortin; Anne Sgard; Magalie Franchomme (Développement Durable et Territoires)
Looking at considering landscape as an object or a tool for governance allows us to set a milestone in recent trends where observation and critical analysis of territorial governance modalities are refined. It also confirms the extension of the landscape field beyond remarkable and heritage landscapes in order to analyse management of the everyday landscape in public policies. When approached from a governance perspective, landscape is part of a political questioning regarding : actors, power relations, decision-making processes and management logics. Confronting governance and landscape therefore encourages us to focus attention on a set of epistemological, political and methodological issues. The dossier "Landscape as an instrument of territorial governance : between experimentation, criticism and institutional capacities" brings together eleven texts that have responded to this invitation, all based on case studies, at different scales, to observe, decipher and test forms of governance of, by or for landscape.